The Challenges and Opportunities of the Merdeka Belajar Policy in Higher Education: The Prospects for Its Implementation - Wiwin Windiana; Kamalatan Nihaya; Muhammad Iqbal Nugraha (UIN Sunan Gunung Djati Bandung, 2024)
Permendikbudristek number 12 year 2024, explains that the Merdeka curriculum includes the basic curriculum framework and curriculum structure. It exists because Curriculum 13 (Kurtilas) sets standards but can be rigid, limiting schools' flexibility to adapt to local needs and student interests. This research aims to analyze further and beyond the challenges and opportunities of the Merdeka Belajar curriculum for the prospects of future curricula and the prospects of the Merdeka Belajar curriculum itself. This research used a systematic literature review from 34 highly regarded global and national indexes and computerized databases accessible via Scopus Dimension accounts. Data analysis in this paper entails the process of inspecting, filtering, and modeling data to discover useful information, draw conclusions, and support decision-making. The finding shows the diffusion of innovation of the Merdeka Belajar curriculum adopted from Roger’s theory (2003). The main challenges are curriculum adjustment, funding, and partnership exploration. While the opportunities are producing academically competent graduates and skills in the face of technological challenges and society’s expectations, independent learning, enhancing students’ competency in soft and hard skills as human capital that fits the age of digital technology, as well as inviting various partners and universities and providing a range of learning experiences and networking options for students.